2012
DOI: 10.1007/s11116-012-9415-8
|View full text |Cite
|
Sign up to set email alerts
|

How can we alter our carbon footprint? Estimating GHG emissions based on travel survey information

Abstract: The City of Montreal has taken recent initiatives to significantly reduce overall greenhouse (GHG) emissions from the transport sector and has made large investments in alternative transportation. In particular, the City has called upon the participation of all businesses and institutions to further these goals. In light of these recent plans, this study identifies with two objectives: first, to develop a methodology for estimating GHG emissions generated by commuters to McGill University's downtown campus; an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 10 publications
1
14
0
5
Order By: Relevance
“…The average passenger car, representing the vehicle age distribution of cars in Montreal, emits between 180 and 650 g of CO 2 equivalent (CO 2 eq) per kilometer [33]. Environment and Climate Change Canada estimates the social cost of carbon (SCC) at $41/ton ($33 US/ton) [34].…”
Section: Perception Of Travel-related Fuel and Environmental Costsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average passenger car, representing the vehicle age distribution of cars in Montreal, emits between 180 and 650 g of CO 2 equivalent (CO 2 eq) per kilometer [33]. Environment and Climate Change Canada estimates the social cost of carbon (SCC) at $41/ton ($33 US/ton) [34].…”
Section: Perception Of Travel-related Fuel and Environmental Costsmentioning
confidence: 99%
“…Using an average car load factor of 1.6 [35], this would result in GHG social cost between $0.005/km ($0.004 US/km) and $0.02/km ($0.016 US/km). The Société de transport de Montréal, the public transport agency operating the buses and metro systems in Montreal, reports that each bus emits approximately 1600 g CO 2 eq/km while accommodating 40 passengers on average in the morning [33]. This results in 40 g CO 2 eq/km per passenger.…”
Section: Perception Of Travel-related Fuel and Environmental Costsmentioning
confidence: 99%
“…For example, Ko et al (2011) have reported that on average, each person emits about 1.6 kg CO 2 a day in Seoul. In contrast, this level of CO 2 emission was reported for a single trip to McGill University for different groups (Mathez et al 2013). Our weekly finding was found to be slightly higher than the previously reported rates, which suggests that people in rural areas emit more CO 2 per capita.…”
Section: Resultsmentioning
confidence: 64%
“…As a result, researchers have started using disaggregate measures in order to understand the complexity and patterns of CO 2 emissions associated with personal travel. The use of household travel survey data (HTSD) has been identified as the most effective way of modelling the complexity of CO 2 emissions in these studies (see Brand and Preston 2010;Darido et al 2014;Ko et al 2011;Mathez et al 2013). Ko et al (2011) have identified groups of high CO 2 emitters in the Seoul Metropolitan Area using the 2006 HTSD.…”
Section: Measures Of Co 2 Emissions From Road Transportmentioning
confidence: 99%
See 1 more Smart Citation